Spiritual Intelligence as a Moderator in Village Fund Fraud Prevention - Nurcahya, Yulida Army; Prihastiwi, Diah Agustina; Fatimah, Ari Nurul (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Spiritual intelligence is seen as a psychological strength that can strengthen integrity values ​​and prevent rationalization of unethical actions. This study aims to examine the role of spiritual intelligence as a moderating variable in the relationship between the effectiveness of internal control, ethical behavior, and the competence of village officials in preventing misappropriation of village funds. This study uses a quantitative approach with data collection through questionnaires distributed to 49 village officials in areas with the highest village fund allocations. Respondents consisted of village heads, village secretaries, and heads of affairs. The analysis technique used was Moderated Regression Analysis (MRA) with the help of SPSS software. The results of the study indicate that the effectiveness of internal control, ethical behavior, and the competence of village officials have a significant effect on preventing misappropriation of village funds. Spiritual intelligence is proven to moderate the relationship between internal control and competence with fraud prevention, but not on ethical behavior. This study provides a practical contribution to strengthening village financial governance based on spiritual values. For further research, it is recommended to integrate a qualitative approach and consider local cultural factors and social dynamics in order to gain a deeper understanding of preventing public fund fraud.